Shear strengthening of concrete members with TRM jackets: Effect of shear span-to-depth ratio, material and amount of external reinforcement - Tetta, Zoi C.; Koutas, Lampros N.; Bournas, Dionysios A. (Elsevier, 2018)
An experimental work on reinforced concrete (RC) rectangular beams strengthened in shear with textile reinforced mortar (TRM) jackets is presented in this paper, with focus on the following investigated parameters: (a) the amount of external TRM reinforcement ratio, ρf, by means of using different number of textile layers and different types of textile fibre materials (carbon, glass, basalt); (b) the textile geometry, and (c) the shear span-to-depth ratio, a/d. In total, 22 tests were conducted on simply supported rectangular RC beams under (three-point bending) monotonic loading. The experimental results revealed that: (1) TRM is very effective when the failure is attributed to debonding of the TRM jacket from the concrete substrate; (2) the trend of effective strains for carbon, glass and basalt TRM jackets is descending for increasing values of the TRM reinforcement ratio, ρf, when failure is associated to debonding of the jacket; (3) the effect of textile geometry is significant only for low values of ρf, resulting in variances in the capacity enhancement and the failure modes, and (4) the shear span-to-depth ratio has practically no effect to the failure mode nor to the TRM jacket contribution to the total shear resistance of the RC beams.